1980
DOI: 10.1002/jlac.198019801012
|View full text |Cite
|
Sign up to set email alerts
|

Strukturuntersuchungen an Oxadiazolring‐Systemen

Abstract: Nach der Umsetzung von p-Hydroxyphenylzimtsaure 7 mit HNO, wurden die Verbindungen 10 bis 15 isoliert und spektroskopisch charakterisiert. Das in der Literatur vermeintlich als 1,2,3-Oxadiazol-3-oxid 5 beschriebene Produkt ist nach der Rontgenstrukturanalyse das Furoxan 10.Es kristallisiert in der Raumgruppe E , / c [a = 6.894, b = 9.000, c = 12.675 A und B = 102.59"' (2 = 4); R = 0.066 fur 1272 symmetrieunabhangige Reflexe mit I 5 2 a (I)]. Bei der um einen Sauerstoff armeren Verbindung 11 handelt es sich urn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
5
8
0
Order By: Relevance
“…Apparently artifacts formed from reactions on the chromatography column. Preliminary '"C NMR, 'H NMR and IR data for the reaction mixture was very similar to those reported by Hanefeld and Gunes (1986) and Plucken et al (1980) useful for other applications using different processing conditions. Careful control of the screw configuration, die design and barrel temperatures could result in a wide variety of desirable products and could overcome many of the limitations previously reported.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Apparently artifacts formed from reactions on the chromatography column. Preliminary '"C NMR, 'H NMR and IR data for the reaction mixture was very similar to those reported by Hanefeld and Gunes (1986) and Plucken et al (1980) useful for other applications using different processing conditions. Careful control of the screw configuration, die design and barrel temperatures could result in a wide variety of desirable products and could overcome many of the limitations previously reported.…”
Section: Resultssupporting
confidence: 83%
“…Apparently artifacts formed from reactions on the chromatography column. Preliminary '"C NMR, 'H NMR and IR data for the reaction mixture was very similar to those reported by Hanefeld and Gunes (1986) and Plucken et al (1980) for N-nitroso compounds. Further work is needed to RESTRUCTURING OF DEBONED CHICKEN... useful for other applications using different processing conditions.…”
Section: Isolation and Identification Of Volatiles (Gs-ms)supporting
confidence: 71%
“…( E) -2,3-Bis(4-hydroxyphenyl)but-2-enedinitrile (( E )-37). Dicyanostilbene ( E )- 32 (25 mg, 0.0861 mmol) was demethylated with BF 3 ·SMe 2 according to method D. Flash chromatography (10% MeOH/CH 2 Cl 2 ) and recrystallization from MeOH/H 2 O gave ( E )- 37 as a yellow solid (24 mg, quantitative yield): mp 274−276 °C dec (lit . mp 287−288 °C dec); 1 H NMR (500 MHz, acetone- d 6 ) δ 9.22 (br s, 2H), 7.74 (AA‘ of AA‘XX‘, J AX = 8.8, J AA ‘ = 2.5, 4H), 7.03 (XX‘ of AA‘XX‘, J AX = 8.8, J XX ‘ = 2.5, 4H); 13 C NMR (125 MHz, acetone- d 6 ) δ 161.1, 131.5, 124.9, 123.6, 118.1, 116.8; MS (EI) m / z 262 (M + , 100).…”
Section: Methodsmentioning
confidence: 99%
“…H2SO4 (1 mL) was added to anhydrous 1 (1.0 g, 6 mmol) dissolved in 23 mL of anhydrous MeOH and refluxed under N2 for 2 h at 45 °C. The reaction was monitored by TLC (system E, Rf 0.57, dark orange), which indicated that 3-(4-hydroxyphenyl)-2-propenoic acid methyl ester (16) was produced in about 80% yield after 3.5 h. The reaction mixture (30 mL) was poured over 24 g of crushed ice and stirred until the ice dissolved and the solution became milky white. The pH was adjusted to 8.0 with 78 mL of 1 M NaHCO 3, and the solution was extracted with 3 × 130 mL CH2Cl2.…”
Section: (E)-and (Z)-1′4-dihydroxybenzeneacetaldehyde Oxime [(E)-and ...mentioning
confidence: 99%
“…Previous studies concerned with the nitrosation of 1 were all conducted in organic/aqueous mixtures and not over a range of reaction pH. The two major products of the reaction of 1 with nitrite at 0 °C in acetone/H 2 O (1: 2, v/v) were identified as 4-hydroxy-1′-oxo-benzeneacetaldehyde aldoxime (7) and 4-(2-oxido-1,2,5-oxadiazol-3-yl)phenol (13) in 50 and 43% yields, respectively (16). Products of the reaction of 1 with nitrite in EtOH/H 2 O (1:1, v/v) at room temperature were characterized as 4-hydroxybenzaldehyde (3, 13%), 4-(2-oxido-1,2,5-oxadiazol-4-yl)phenol (3%), 4-hydroxy-1′-(hydroxyimino)benzeneacetaldehyde (2%), and an unidentified product of molecular mass 163 (C 8 H 5 NO 3 ) (17).…”
Section: Introductionmentioning
confidence: 99%